COVID-19 and Food Safety FAQ: Is Coronavirus a Food Safety Issue? (Mandarin Chinese) - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
This is the Mandarin Chinese translation of FSHN20-18/FS341: COVID-19 and Food Safety FAQ: Is Coronavirus a Food Safety Issue?. It provides guidance related to COVID-19 regarding food production, handling, and packaging. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman, and published by the UF/IFAS Food Science and Human Nutrition Department, May 2020.